Diego Velázquez's Kings, Buffoons and Philosophers in the Context of His Religious Paintings: the View from Russia (Philosophical-Anthropological Analysis) - M. Silantieva (Vestnik MGIMO-Universiteta)
The article is dedicated to the analysis of philosophic anthropology of the great Spanish artist of the 17th century Diego Velazquez. This anthropology is considered through the prism of the problems that set the life of contemporary Russia and its "reflections" in the present-day Russian artists' works. At that Velazquez's philosophical anthropology is reconstructed on the basis of his works. As a consequence, significant part of attention is paid to the method that allows performing such reconstruction. The author proceeds from the belief according to which not only written texts can be considered philosophically. The visual "texts" connected with certain world outlook component of art creative work undoubtedly possess definite semantics. Expressed by the language of art, such image lines contain intelligible sense component reconstruction of which can be subjected to strict scientific and philosophical analysis and corrected with its help. At that one should not think that the images are "translated" into "the text of words" - on the contrary, philosophical reconstruction implies not as "verbalization" of visual line as coherent to it logical mastering of the picture's sense (in this case) against the background of historical and historical-philosophical "scenery". The urgency of turning to this problem is brought about by the fact that a number of questions that found vivid and coherent (as philosophical-anthropological research shows) embodiment in Velazquez's creative work are extremely interesting for contemporary thinkers speaking the language of contemporary fine arts. "The topic of mirror" is among such questions and it deals with correlation of intellectual and rational in a person's consciousness, and, finally, there is the issue of the man as a bearer of moral principles. Comparison of attitudes shown by contemporary painting with Velazquez's ideas enables to trace the development of philosophical anthropology and in the area of its most significant categories - the man, society, consciousness, corporality, creative work, etc.